Limited Clinical Utility of Non-invasive Prenatal Testing for Subchromosomal Abnormalities. Issue 4 (April 2016) - Lo, Kitty K.; Karampetsou, Evangelia; Boustred, Christopher; McKay, Fiona; Mason, Sarah; Hill, Melissa; Plagnol, Vincent; Chitty, Lyn S.
Abstract : Obstet Gynecol Surv 2016;71(4):211–213 Since 2011, the use of massively parallel sequencing of cell-free DNA (cfDNA) in maternal plasma for noninvasive prenatal testing (NIPT) of fetal aneuploidies has become available in more than 60 countries.